A particular focus on the prevalence of α-thalassemia and β-thalassemia among pregnant women in Changsha County, Hunan Province - Xia, Yu; Huang, Cailian; Yang, Mudan; Zhang, Meng; Lu, Yang (Frontiers in Genetics, 2024)
BackgroundThalassemia is a inherited monogenic blood disorder and more prevalent in southern China. In this study, Our aim was to elucidate the molecular spectrum and phenotypic features of thalassemia in pregnant women in Changsha County.MethodsNext-generation sequencing (NGS) was conducted for 38,810 pregnant women to diagnose thalassemia in Changsha County. Further analysis of hematological parameters was conducted on subjects who had not previously undergone thalassemia screening in other hospitals.ResultsIn this study, 2,208 (5.69%) pregnant women were diagnosed as carriers of thalassemia using NGS analysis. Among 1,594 cases of α-thalassemia, 23 genotypes were identified, and among 578 cases of β-thalassemia, 22 genotypes were detected. Additionally, 18 genotypes were detected among 36 cases of composite α- and β-thalassemia. Among all carriers of thalassemia, 8 rare α-mutations and 11 rare β-mutations were found in the study population. Notably, pregnant women diagnosed as carriers of thalassemia tended to have lower hemoglobin levels. Furthermore, multivariable logistic regression analysis indicates that the values of MCV and MCH have the greatest impact on genetic diagnosis.ConclusionOur study has provided detailed genotypes and hematological parameters of thalassemia in pregnant women in Changsha county and reveal that certain abnormal blood parameters have a remarkably impact on genetic diagnosis results. Furthermore, our data suggest that combining hemoglobin electrophoresis and NGS provides a powerful tool for prenatal diagnosis, which will increase the accuracy of clinical diagnosis of thalassemia.